PROSES PENCIPTAAN KARYA TARI UNBALANCED - Dewi, Septiana; Supendi, Eko (Institut Seni Indonesia Surakarta, 2023)
Unbalanced is a dance work composed by Septiana Dewi in 2022 and performed at the Great Theater Building of the Indonesian Institute of the Arts in 2023. The Unbalanced dance work was inspired by the empirical experience of a deaf and mute person named Irfan Nurdiawan, a disabled athlete. Irfan Nurdiawan has had hearing loss since birth. However, Irfan tries to show others that he can also achieve like other normal children. The Unbalanced dance work is in the form of a group with five female dancers and Septiana Dewi as a dancer and choreographer. In the process, the dancers try to feel what kind of experience a deaf and mute person feels by covering their ears in a closed room and also in a crowded environment. This study is intended to describe the form of the Unbalanced dance work performance and the process of creating the Unbalanced dance work. The description of the form of the Unbalanced dance performance uses the theory of Slamet MD in his book entitled melihat Tari in 2016, and the process of creating the Unbalanced dance work uses the theory of Alma M. Hawkins quoted by Bambang Pudjasworo et al in the book Karya Cipta Seni Pertanggungaan in 2017. The method used in this study is qualitative research which includes observation, interviews and documentation. The results obtained in this study are in the form of a description of the form of performance consisting of movement, dancers, costume make-up, floor patterns, dance music and the place where the Unbalanced dance work is performed as well as the process of creating the Unbalanced dance work.